2019
DOI: 10.2147/ott.s198126
|View full text |Cite
|
Sign up to set email alerts
|

<p>M2 macrophages confer resistance to 5-fluorouracil in colorectal cancer through the activation of CCL22/PI3K/AKT signaling</p>

Abstract: Background: M2 macrophages are crucial components of tumor microenvironment that frequently associated with the resistance of therapeutic treatments in human cancers, but their role in the chemosensitivity of colorectal cancer (CRC) to 5-fluorouracil (5-FU) is still obscure. Methods: In our study, we clarified the biological functions of M2 macrophages and their mechanism on the chemosensitivity of CRC cells to 5-FU. Then, we analyzed the correlation between CCL22 and CD68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 39 publications
4
68
0
Order By: Relevance
“…CCL22 was found in macrophages of tongue squamous cell carcinoma [46]. Additionally, the secretion of CCL22 by M2-like macrophages in colorectal cancer was proven [32]. However, CCL22 expression in cervical cancer has not been previously determined.…”
Section: Discussionmentioning
confidence: 96%
“…CCL22 was found in macrophages of tongue squamous cell carcinoma [46]. Additionally, the secretion of CCL22 by M2-like macrophages in colorectal cancer was proven [32]. However, CCL22 expression in cervical cancer has not been previously determined.…”
Section: Discussionmentioning
confidence: 96%
“…In vitro putrescine (polyamine) secreted by TAMs significantly attenuated 5-FU-induced growth inhibition of SW-480 and HCT-116 cell lines (143). 5-FU treatment induces CCL22 secretion by M2 macrophages in vitro (144). Co-culture of colon cancer cells and M2 macrophages treated with 5-FU indicated that macrophages mediate cell migration and invasion in CRC cells inducing EMT and activating PI3K/AKT pathway (144).…”
Section: Tams and Colorectal Cancer Treatmentmentioning
confidence: 99%
“…5-FU treatment induces CCL22 secretion by M2 macrophages in vitro (144). Co-culture of colon cancer cells and M2 macrophages treated with 5-FU indicated that macrophages mediate cell migration and invasion in CRC cells inducing EMT and activating PI3K/AKT pathway (144). CCL22 neutralizing antibody increased the apoptosis in cancer cells.…”
Section: Tams and Colorectal Cancer Treatmentmentioning
confidence: 99%
“…Through literature research, CCL22 was identi ed as up-stream regulator of PI3K/AKT pathway. Secreted by M2 macrophages, CCL22 regulates CRC cells' epithelial-mesenchymal transition (EMT), and promotes tumor's resistance to chemotherapy 29,30 . FLOT1 also induces EMT and alters cell cycle by modulating Erk/Akt signaling axis 31 .…”
Section: Discussionmentioning
confidence: 99%